2013
DOI: 10.1016/j.jcv.2013.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of residual perinatal transmission of hepatitis B virus (HBV) and of genetic variants in human immunodeficiency virus and HBV co-infected women and their offspring

Abstract: Background Despite implementation of universal infant hepatitis B (HB) vaccination, mother-to-child transmission (MTCT) of hepatitis B virus (HBV) still occurs. Limited data are available on the residual MTCT of HBV in human immunodeficiency virus (HIV)-HBV co-infected women. Objectives We assessed the prevalence of HBV infection among HIV-infected pregnant women and the rate of residual MTCT of HBV from HIV-HBV co-infected women and analyzed the viral determinants in mothers and their HBV-infected children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In this study, we found that maternal HBeAg positivity and HBV DNA >10 6 copies/mL contributed significantly to the trans-placental transmission, which is quite consistent with the risk of failure to the immunoprophylaxis [23][24][25][26][27]. The trans-placental transmission was more frequent in the mothers with genotype B2 and those younger than 27 years, possibly because of their higher viral load and/or HBeAg positivity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, we found that maternal HBeAg positivity and HBV DNA >10 6 copies/mL contributed significantly to the trans-placental transmission, which is quite consistent with the risk of failure to the immunoprophylaxis [23][24][25][26][27]. The trans-placental transmission was more frequent in the mothers with genotype B2 and those younger than 27 years, possibly because of their higher viral load and/or HBeAg positivity.…”
Section: Discussionsupporting
confidence: 80%
“…Antiviral treatment at the late stage of pregnancy has been proven to be effective in reducing HBV MTCT [28]. Our data, together with others' [23][24][25][26][27], are important in identifying the HBsAg-positive mothers who are more likely to develop MTCT and need antiviral treatment at the late stage of pregnancy.…”
Section: Discussionmentioning
confidence: 52%
“…Similar to many SSA countries, Uganda's expanded program on immunization (UNEPI) integrated the HBV vaccination in its schedule in 2002 [11] with the first vaccine dose included in a pentavalent vaccine given at the age of six weeks and the second and third dose at 10 and 14 weeks respectively [12]. Currently, the HepB3 coverage in Uganda is about 78% [13].…”
Section: Introductionmentioning
confidence: 99%
“…The OLA was evaluated by testing plasma from individuals known to be chronically HBV infected and treated with 3TC for 1–8.5 years who were enrolled in the multicenter HIV Prevention and Treatment cohort (ClinicalTrials.gov NCT00433030) in Thailand (Khamduang et al, 2013, 2012). DNA was extracted from participants’ plasma using an automatic sample extraction system (Abbott M2000sp).…”
mentioning
confidence: 99%
“…OLA probes to detect mutations encoding rtL180M and rtM204V/I were designed to accommodate common genetic variations using alignments of HBV sequences from subjects residing in Thailand (Khamduang et al, 2013, 2012) (Table 1). Wild-type and mutant plasmids, generated by cloning subjects’ amplicons (TOPO ® TA Cloning ® Kit for Sequencing, Invitrogen, Carlsbad, CA), were mixed at 2, 5, 10, 25, 50, 75, 90, and 95% mutant, and used to quantify the proportion of mutants in the clinical specimens.…”
mentioning
confidence: 99%